2016
DOI: 10.1530/erc-15-0540
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory therapies in TRAMP mice: delay in PCa progression

Abstract: The aim of this study was to characterize the structural and molecular biology as well as evaluate the immediate and late responses of prostatic cancer in the transgenic adenocarcinoma of the mouse prostate (TRAMP) model after treatment with goniothalamin (GTN) and celecoxib. The treated mice received GTN (150 mg/kg, gavage) or celecoxib (10 mg/kg, gavage) from 8 to 12 weeks of age. They were killed at different ages: the immediate-response groups at 12 weeks and the late-response groups at 22 weeks. The ventr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
2
8

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 30 publications
(69 citation statements)
references
References 54 publications
7
52
2
8
Order By: Relevance
“…Regarding the mitogenic process, studies showed higher IGFR1 in the prostatic stroma close to tumor epithelial cells and also an increased expression in the prostate ventral lobe in older TRAMP mice (Ryan et al, 2007;Kido et al, 2016). In addition, other studies indicated that increased IGFR1, around tumoral areas, is related to increased genic transcription level, due to IGF1 signaling, which promotes prostate epithelial proliferation (Hellawell et al, 2002;Yu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the mitogenic process, studies showed higher IGFR1 in the prostatic stroma close to tumor epithelial cells and also an increased expression in the prostate ventral lobe in older TRAMP mice (Ryan et al, 2007;Kido et al, 2016). In addition, other studies indicated that increased IGFR1, around tumoral areas, is related to increased genic transcription level, due to IGF1 signaling, which promotes prostate epithelial proliferation (Hellawell et al, 2002;Yu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In each quadrant, the prostate tissue was classified in: healthy epithelium (HE); low-grade prostatic intraepithelial neoplasia (LGPIN); high-grade prostatic intraepithelial (HGPIN), and well-differentiated adenocarcinoma (WDA) (modified from Berman-Booty et al, 2012;Kido et al, 2016;Silva et al, 2017). Thus, the morphological analyses were made based on the observation of eight random and non-overlapping microscopic fields under 400 magnification per animal.…”
Section: Light Microscopymentioning
confidence: 99%
“…Racemic GTN, a styryl lactone found in its R configuration in plants of the genus Goniothalamus, Annonaceae, has in vitro antiproliferative activity in human tumor cell lines via activation of apoptosis (18)(19)(20)23,38). GTN also presents general anti-inflammatory effects, without side effects (as seen with aspirin, for example) in the therapeutic doses (20,22,39). Although the intake of aspirin can prevent CRC development, it can cause serious health problems, such as stomach bleeding, due to inhibition of cyclooxygenases (COX) 1 and 2 (40).…”
Section: Discussionmentioning
confidence: 99%
“…In order to assess the effects of short and long‐term treatment, the animals were treated from 8 to 12 weeks of age, and euthanized at different times: the immediate‐response groups at 12‐week‐old (CEL1 or GTN1) and the late‐response groups at 22 weeks‐old (CEL2 or GTN2). Celecoxib Treatment: CEL1 (n = 10) and CEL2 (n = 10) groups received a 10 mg/kg Celecoxib dose orally five times a week for 30 days only (from 8 to 12‐week old mice [Kido et al, ]). Goniothalamin Treatment: GTN1 (n = 10) and GTN2 (n = 10) groups received a 150 mg/kg GTN dose orally, three times a week for 30 days only (from 8 to 12‐weeks old mice) (Kido et al, ).…”
Section: Methodsmentioning
confidence: 99%